Synthesis and thermal stability of a novel acetylene end-capped silicon-containing polyimide coupling agent with a silane pendant group. (November 2019) - Yang, Teng; Hu, Yanhong; Deng, Shifeng; Du, Lei; Zhou, Jiali; Hu, Junjie; Jian, Xue
In this study, a novel heat-resistant polyimide macromolecular coupling agent (PSI-C) was designed and synthesized. Silicon-containing diamine was one of the monomers used to increase the solubility of the polyimide, and m -aminophenylacetylene was the end-capping reagent that copolymerized with the resin matrix. A silane coupling group was introduced into the side chain to match the reinforced fiber. Thermogravimetric analysis revealed that the 5% thermal decomposition temperature ( T d5 ) of the cured PSI-C could reach 454°C and the residual rate at 800°C was 53%. Thermal pyrolysis of the vaporized resin showed that the heat-resistant functional group was still detectable at 550°C. The thermal stability of the alkynyl-terminated silicon-containing polyimide silane coupling agent was higher than those of conventional silane coupling agents. The curing process of the composite system was not affected when adding the coupling agent PSI-C to the quartz fiber/alkynyl resin composite. The interlaminar shear strength and bending strength of the composite were increased by 55% and 61%, respectively, at room temperature. The high-temperature retention rate at 500°C reached 58% and 63%.